INOVASI KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENDORONG PENANAMAN NILAI-NILAI KEARIFAN LOKAL - Andy Riski Pratama; Yulius; Maysa Latifa; Syafrudin; Messy (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
This article discusses the role of innovation in the Islamic Religious Education (PAI) curriculum to strengthen local wisdom values. The curriculum plays a central role in determining the quality of education and the development of student character. In the midst of rapid educational innovation, especially in curriculum development, the challenge for PAI teachers is to adapt to innovations that are often top-down. However, the integration of local wisdom values in the PAI curriculum provides significant added value, not only in deepening the understanding of Islam in the local context, but also in enriching students' educational experience with noble values that can be applied in daily life. This study uses a literature to synthesize information about the concept of PAI curriculum innovation and the importance. The integration of local wisdom in PAI curriculum not only enhances students' engagement in learning, but also strengthens their religious identity in a diverse social and cultural context. In addition, this approach enriches students' with values such as environmental stewardship and gotong royong, which are important in shaping individuals who are responsible and caring towards society. This article concludes that PAI curriculum innovation that integrates local wisdom values not only strengthens Islamic religious education.